1978
DOI: 10.3171/jns.1978.48.1.0085
|View full text |Cite
|
Sign up to set email alerts
|

Acute fractures of the odontoid process

Abstract: ✓ Between 1969 and 1974, 45 cases of acute odontoid fracture were diagnosed and treated at this institution. The group consisted of 35 men and 10 women; 24 were between 19 and 40 years of age, and 21 were over 40 years old. Detectable myelopathy was appreciated in eight cases (18%). Diagnosis was established within 72 hours of the traumatic event. Initial evaluation disclosed displacement of the fracture in 17 cases (38%). Following reduction, the initial treatment was posterior fusion in three cases, and exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
81
0
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(99 citation statements)
references
References 37 publications
8
81
0
10
Order By: Relevance
“…In the younger group they are often secondary to high-energy trauma as motor vehicle accidents. The second peak in the incidence of odontoid fractures is in the elderly, where they appear as a result from low-energy injuries, such as falls from standing height [4,12,13,19]. Abstract During skeletal development the two ossification centers of the odontoid process are separated from the corpus of the axis by a subdental synchondrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the younger group they are often secondary to high-energy trauma as motor vehicle accidents. The second peak in the incidence of odontoid fractures is in the elderly, where they appear as a result from low-energy injuries, such as falls from standing height [4,12,13,19]. Abstract During skeletal development the two ossification centers of the odontoid process are separated from the corpus of the axis by a subdental synchondrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several surgical options are available, but there is no consensus on the best treatment for these fractures. Several authors have suggested more than 4 to 6 mm of dens displacement [6,22], increasing age ([40-65 years) [6,16], posterior odontoid subluxation [16], and comminution of the base of the dens [22] would predict lower rates of fracture union. Therefore, patients with one or more of these criteria or who refuse external immobilization are considered surgical candidates by some surgeons [5].…”
Section: Discussionmentioning
confidence: 99%
“…Reported healing after external immobilization has varied widely from 7% to 100% [26][27][28]. In most series, however, reported rates of successful healing ranged from 37% to 75% [3,6,13,38].…”
Section: Introductionmentioning
confidence: 99%
“…Since several authors reported on a morbidity and mortality of geriatric patients following external cervicothoracic immobilization of OF equalling that of surgical treatment [38][39][40], we also prefer surgical treatment of unstable and/or dislocated Type II and III OF for the purpose of faster recuperation and better clinical results. In the light of significant non-union rates of up to 93% [2,4,7,10,11,[41][42][43][44][45][46][47][48][49][50][51] and a fourfold higher risk to suffer from pulmonary or cardiac complications for an elderly patient immobilized in a Halo Thoracic Vest (HTV) for OF treatment [39], a semi-rigid cervical collar is recommended as non-surgical treatment of stable and non-displaced OF or if surgical treatment is not contrivable due to the general state of health. Recently, usage of the semi-rigid cervical collar was shown to confer a comparable capacity in limiting motion at C1-2 if compared to the HTV [12].…”
Section: Discussionmentioning
confidence: 99%